Characteristics and Source Apportionment of VOCs in a City with Complex Pollution in China - Yu Wang; Guang Yang; Litao Wang; Le Zhao; Shangping Ji; Mengyao Qi; XiaoHan Lu; Zhentong Liu; Jingyao Tan; Yingying Liu; Qing Wang; Ruiguang Xu (Aerosol and Air Quality Research)
Abstract Volatile organic compounds (VOCs) are important precursors in the formation of ozone (O3) and secondary organic aerosol (SOA). Hence, using an online monitor, we measured the concentrations of 56 VOC species in Handan, one of the most polluted cities in China, from Sep. 2017 till Aug. 2018. We also characterized the VOC pollution by measuring the O3 and NOx and determining the chemical reactivity of the VOCs at different levels of O3 pollution, analyzing the regional O3 formation mechanisms, and apportioning the VOC sources. The daily VOC concentrations displayed a wide range, from 37.7 to 288.9 µg m–3, with an average of 112.0 ± 45.5 µg m–3, during the observation period, and the contribution of alkenes and other aromatics to the O3 formation potential (OFP) of the VOCs was higher on medium pollution days than clean days. Furthermore, the majority of the O3 during spring and winter was formed in VOC-sensitive regimes, whereas the high diurnal concentrations during summer and autumn were produced in NOx-sensitive regimes. Based on the i-butane/n-butane and i-propane/n-propane ratios, the main sources of butane and propane were vehicular exhaust and liquid gasoline, respectively. Source apportionment by principal component analysis (PCA) revealed that the VOCs in Handan originated from vehicular emission, industrial production, solvent use, gasoline evaporation, and combustion.